Effects of high carbon dioxide concentration on oil palm growth and development - Shahabuddin, Nur Amanina (2020)
The current atmospheric CO2 level is increasing annually and may affect plant growth, physiology and productivity. A CO2 enrichment study on oil palm clone P164 using Open Top Chamber (OTC) technique was conducted to evaluate the effects on oil palm growth, physiology, bunch production and oil quality. The palms were grown in OTC with two types of CO2 levels; 600 ppm (CO2-enriched) and ambient CO2 level (control) and planted in the field under normal conditions (absolute control). After six years of observation, CO2-enriched palms showed a higher biomass percentage of 22.6% to 23.7% compared to control and absolute control palms. The increase in biomass was contributed by rachis length and trunk height with a reading of 689.63 ± 7.70 cm and 201.25 ± 10.18 cm respectively. This positive growth can be attributed to higher photosynthetic rate of 23.51 ± 0.57 μmolm-2 s -1 and affecting the water use efficiency of 5.33 ± 0.10 μmolmol-1 CO2. Control palms showed the highest bunch weight (kg), meanwhile absolute control palms showed the highest fruit to bunch ratio (%) over five-year period. However, there was no significant difference in fatty acid compositions (FAC), iodine value and carotene content extracted from fruit bunches of all treatments. Under high CO2 level, clonal palm leaves had reduced percentage of nitrogen (N), phosphorous (P) and potassium (K). Enhanced photosynthetic rate due to high CO2 level markedly increased clonal palm growth and biomass. Valuable information of this study may be beneficial for the oil palm industry to develop suitable mitigation strategies in the future.